2016
DOI: 10.1021/acsami.6b02778
|View full text |Cite
|
Sign up to set email alerts
|

Color-Tunable and Highly Luminous N3–-Doped Ba2–xCaxSiO4−δN2/3δ:Eu2+ (0.0 ≤ x ≤ 1.0) Phosphors for White NUV-LED

Abstract: In the search for well-defined phosphor materials for white NUV-LEDs, the highly enhanced luminous efficacy by N(3-) doping as well as color tunability via Ca substitution has been successfully obtained in Ba2-xCaxSiO4-δN2/3δ:Eu(2+) (x = 0.0, 0.5, 0.8, 1.0) phosphors. With increasing Ca-substitution rate, the crystal structures of the phosphor materials are changed from the primitive orthorhombic structure to the hexagonal one, so that the CIE coordinates move from bluish-green (at Ca = 0.0), to blue (at Ca = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The emission intensities at 150 • C greatly were decreased to about 40% of the initial one at ambient temperature, as previous research [44,45]. Kim et al reported that thermal stability of Ba 2−x Ca x SiO 4 :Eu 2+ (x = 0.5) phosphor were highly increased in comparison to that of Ba 2 SiO 4 :Eu 2+ phosphor [46]. Their results probably indicate that the thermal stability of phosphors is very closely related to the structural factor of the phosphors because Ba 2 SiO 4 :Eu 2+ phosphor with orthorhombic phase (space group = Pmcn) [11] was transformed into the hexagonal phase (space group = P3m1) [47] after partial Ca 2+ substitution for Ba 2+ .…”
Section: Photoluminescence Spectrasupporting
confidence: 80%
“…The emission intensities at 150 • C greatly were decreased to about 40% of the initial one at ambient temperature, as previous research [44,45]. Kim et al reported that thermal stability of Ba 2−x Ca x SiO 4 :Eu 2+ (x = 0.5) phosphor were highly increased in comparison to that of Ba 2 SiO 4 :Eu 2+ phosphor [46]. Their results probably indicate that the thermal stability of phosphors is very closely related to the structural factor of the phosphors because Ba 2 SiO 4 :Eu 2+ phosphor with orthorhombic phase (space group = Pmcn) [11] was transformed into the hexagonal phase (space group = P3m1) [47] after partial Ca 2+ substitution for Ba 2+ .…”
Section: Photoluminescence Spectrasupporting
confidence: 80%
“…Comparing with the cation substitution, nitridation of phosphors provides new inspiration to phosphors design . A well‐known fact is that the excellent thermal stability in some nitride phosphors comes from their high covalency and rigidity of structure .…”
Section: Introductionmentioning
confidence: 99%
“…However, the mixing of multi‐phosphors usually results in color imbalance and instability at higher temperatures, limiting their applications. To solve this problem, many efforts have been done to develop single‐phase emission‐tunable (by energy transfer) phosphors pumped with UV or n ‐UV chips . In addition, highly efficient phosphors can not only enhance the energy efficiencies but also present potential advantages in the CCT and CRI.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, many efforts have been done to develop singlephase emission-tunable (by energy transfer) phosphors pumped with UV or n-UV chips. [7][8][9] In addition, highly efficient phosphors can not only enhance the energy efficiencies but also present potential advantages in the CCT and CRI. Thus, novel efficient phosphors for improving the performances of solid-state lighting are interesting.…”
Section: Introductionmentioning
confidence: 99%